2020
DOI: 10.5194/wes-5-427-2020
|View full text |Cite
|
Sign up to set email alerts
|

Analytical model for the power–yaw sensitivity of wind turbines operating in full wake

Abstract: Abstract. Wind turbines are designed to align themselves with the incoming wind direction. However, turbines often experience unintentional yaw misalignment, which can significantly reduce the power production. The unintentional yaw misalignment increases for turbines operating in the wake of upstream turbines. Here, the combined effects of wakes and yaw misalignment are investigated, with a focus on the resulting reduction in power production. A model is developed, which considers the trajectory of each turbi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 31 publications
0
20
0
Order By: Relevance
“…The uncertainties and sensitivities in this study associated with the wall model, subfilter-scale model, wind turbine model, and ABL characteristics such as boundary layer inversion height were not investigated in detail and are left for future work. More reliable and generalizable estimates for P p (Liew et al, 2020), or generally C p as a function of γ , should be investigated. Future work should also investigate the influence of latitude and geostrophic wind direction on wake steering control performance (Howland et al, 2020b).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The uncertainties and sensitivities in this study associated with the wall model, subfilter-scale model, wind turbine model, and ABL characteristics such as boundary layer inversion height were not investigated in detail and are left for future work. More reliable and generalizable estimates for P p (Liew et al, 2020), or generally C p as a function of γ , should be investigated. Future work should also investigate the influence of latitude and geostrophic wind direction on wake steering control performance (Howland et al, 2020b).…”
Section: Discussionmentioning
confidence: 99%
“…However, simulations have shown for the NREL 5 MW turbine that P p equals 1.88 (Gebraad et al, 2016a). Recent work has shown that P p differs for freestream and waked turbines (Liew et al, 2020). The value of P p that results in a satisfactory agreement with experimental data depends on the wind turbine model, ABL shear and veer, and atmospheric stability.…”
Section: Lifting Line Wake Modelmentioning
confidence: 97%
See 1 more Smart Citation
“…The power-yaw loss coefficient α is implemented as suggested by the paper of Liew et al [51]. This paper describes how α should be adjusted based on whether a turbine is in the wake of another turbine and what the spacing is between those two turbines.…”
Section: Calibration Methodsmentioning
confidence: 99%
“…For example, Fleming et al ( 2017) estimate p P = 1.43 using data from a commercial wind plant, Gebraad et al (2016) find that a value of p P = 1.88 fits results from LES simulations, and Medici ( 2005) determines a value of p P = 2 from a wind tunnel experiment. But as discussed by Liew et al (2020), blade element momentum theory predicts p P = 3. Note that p P and the value of p v used in FLORIS (see Eq.…”
Section: Impact Of Yaw Misalignment On Power Productionmentioning
confidence: 95%